Coachee-centered Coaching: Toward the Implementation of Learner-centered Learning in The Context of Indonesian 2013 Curriculum - Tarwiyah, Siti (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Coaching is a type of professional development focusing on professional dialogue to build teacher capacity to enhance the success of learning and the quality of education in general. Coachee-centered coaching gives model to the coachees the implementation of learner-centered learning. This paper describes the model of presenting coaching materials through coachee-centered coaching dealing with the implementation of 2013 curriculum in EFL class. The study was designed qualitatively. The data were accessed from 6 teachers of English at State Islamic Junior High School in Semarang-Indonesia (MTsN2 Semarang). The materials and the procedures of implementation were formulated based on need analysis through teaching observation, lesson plan analysis, and Focus Group Discussion. In term of material presentation, the coachee-centered coaching was implemented through such methods as Demonstration, Scientific Approach, Lecturing and Discussion, Problem-Based Learning, Task-Based Learning, Inquiry Learning, Presentation-Practice-Production.